IMPROVING THE METHODS OF EVALUATING THE EFFICIENCY OF CORPORATE MANAGEMENT (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2024)
The main basis of the economic reforms implemented in Uzbekistan since the first years of independence is the expropriation of property from the state and its privatization. Its purpose is to create the basic conditions necessary for the creation of a market economy (formation of the institution of private property, establishment of the economic and legal base and institutional structures without which the private sector of the economy cannot function).